2015
DOI: 10.3389/fncom.2015.00069
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of synchronous activity propagation in neuronal networks driven by local excitation

Abstract: Many experimental and theoretical studies have suggested that the reliable propagation of synchronous neural activity is crucial for neural information processing. The propagation of synchronous firing activity in so-called synfire chains has been studied extensively in feed-forward networks of spiking neurons. However, it remains unclear how such neural activity could emerge in recurrent neuronal networks through synaptic plasticity. In this study, we investigate whether local excitation, i.e., neurons that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…This nucleus is a compelling candidate for a brain area that can organize autonomously to produce structured dynamics, since auditory deprived songbirds generate a song with a stereotypical temporal course [51,52]. However, in almost all theoretical works that addressed how local plasticity rules give rise to temporal sequences of neural activity, it was necessary to provide some form of structured input into the network in order to robustly produce the sequential neural activity [25,[53][54][55]. Similarly, structured inputs were required in order to robustly produce self connected assemblies, which give rise to another useful form of neural dynamics, characterized by multiple stable states [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…This nucleus is a compelling candidate for a brain area that can organize autonomously to produce structured dynamics, since auditory deprived songbirds generate a song with a stereotypical temporal course [51,52]. However, in almost all theoretical works that addressed how local plasticity rules give rise to temporal sequences of neural activity, it was necessary to provide some form of structured input into the network in order to robustly produce the sequential neural activity [25,[53][54][55]. Similarly, structured inputs were required in order to robustly produce self connected assemblies, which give rise to another useful form of neural dynamics, characterized by multiple stable states [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Other models have been proposed for theta phase precession [87][88][89][90] and replay [91][92][93][94][95][96]. For example, one grid cell model uses after-spike depolarization within a 1D continuous attractor network to generate phase precession and theta sequences [89].…”
Section: Relationships To Experiments and Other Modelsmentioning
confidence: 99%
“…Several of them encode replay trajectories into synaptic weights, either through hard-wiring or a learning mechanism [94][95][96]. Two models have suggested that replays originate from wavefronts of activity propagating through networks of place cells [91,93]. These wavefronts then enhance connections through the network though spike-timing-dependent plasticity rules, which could account for the ability of reward to modulate hippocampal replay [21,23].…”
Section: Relationships To Experiments and Other Modelsmentioning
confidence: 99%
“…The dynamics of flocking in birds or schooling in fish and similar behavior in bacteria [8] essentially are examples of synchrony across a large scale determined by local interactions [9][10][11]. At the suborganism scale, how the dynamics of individual neurons lead to collective behavior is a key question in neuroscience [12]. The synchrony of neural oscillators is thought to play an important role in behavior [6] and in various pathologies [13].…”
Section: Introductionmentioning
confidence: 99%